(untitled) (Journal of the College of Basic Education, 2022)
The aim of the research is to know the spatial ability of the geography teachers in the preparatory stage and their relation to their thinking skills. The researcher relied on the descriptive approach and a number of procedures which included the identification of the research community, which was limited to the geographical teachers in the preparatory stage for the academic year 2017-2018, which are (94) teachers and schools. The current research sample included (66) teachers and schools In order to achieve the objectives of the research, the researcher adopted the first tools in the test of spatial ability (20) paragraphs, and the second test of reflective thinking consisting of (50) paragraph, and the researcher extracted their honesty by presenting them to a group of experts Specialists and their stability The researcher concluded that spatial ability and contemplative thinking were effective in the teaching process, stimulating motivation for learners and achieving educational goals. He recommended inviting the Ministry of Education to benefit from the research prepared by the researcher and applying it to the teachers of geography. , And proposed a similar study of this study in other stages of study, and with other variables